ChemInform Abstract: A Prototype Continuous‐Flow Liquid—Liquid Extraction System Using Open‐Source Technology. Issue 9 (5th March 2013) - O'Brien, Matthew; Koos, Peter; Browne, Duncan L.; Ley, Steven V.
Abstract A computer control script is used to monitor three different reactions in a liquid flow reactor via a simple webcam setup.